A HER electrocatalyst with porous heterostructure and preparation method thereof

By introducing RuO2 into CoxP and building a porous heterostructure, the problem of low activity of HER electrocatalysts in the neutral electrolyte in the prior art is solved, and an efficient HER catalytic effect under neutral conditions is achieved.

CN119530872BActive Publication Date: 2025-05-09FUYANG NORMAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510034112.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-05-09
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing HER electrocatalysts have low HER activity in neutral electrolytes, and the use of acidic or alkaline electrolytes has problems with corrosion and environmental pollution.

Method used

By introducing RuO2 into CoxP, the intrinsic HER active site of CoxP is enhanced and the contact area between the catalyst and the electrolyte is increased.

Benefits of technology

An electrocatalyst with excellent HER performance in neutral electrolyte is achieved. The current density of 10mA·cm-2 and 100mA·cm-2 is achieved with only an overpotential of 8mV and 81mV, and it shows good stability at a high current density of 500mA·cm-2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530872B_ABST
    Figure CN119530872B_ABST
Patent Text Reader

Abstract

The present invention discloses a HER electrocatalyst with a porous heterostructure and a preparation method thereof, belonging to the field of HER electrocatalysts. The preparation method is as follows: Using cobalt nitrate hexahydrate, urea, nickel foam, and ruthenium chloride as raw materials, a ruthenium-doped cobalt hydroxycarbonate nanowire array is prepared by a solvothermal method; heating the ruthenium-doped cobalt hydroxycarbonate nanowire array in a muffle furnace to obtain a RuO2 / Co3O4 nanowire array; placing the RuO2 / Co3O4 nanowire array and NaH2PO2 in a crucible and annealing and phosphating in a nitrogen gas stream to obtain a RuO2 / Co x P / Co3O4 nanowire array, and then performing pickling to remove Co3O4 to obtain a RuO2 / Co x P nanowire array, which is the HER electrocatalyst with a porous heterostructure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of HER electrocatalysts, and in particular to a HER electrocatalyst with a porous heterogeneous structure and a preparation method thereof. Background Art

[0002] Most of the HER electrocatalysts reported so far can effectively catalyze HER only under extreme pH conditions (strong acid or strong alkaline electrolytes). However, the use of acidic and alkaline electrolytes has problems such as corrosion of the electrolytic cell, environmental pollution, and the need to use expensive ion exchange membranes. Therefore, if water can be electrolyzed in a neutral electrolyte, ion exchange membranes can be omitted and corrosion problems can be solved, which can not only reduce overall costs but also minimize environmental problems. However, due to factors such as the poor conductivity of neutral electrolytes, the HER activity of the catalyst in neutral electrolytes is significantly lower than its HER activity in strong acids or strong bases. Therefore, there is an urgent need to develop electrocatalysts with excellent HER performance in neutral electrolytes.

[0003] In recent years, transition metal phosphides (TMPs) have attracted much attention due to their advantages such as low cost, high conductivity, good catalytic activity and good stability. x P is considered to be a very promising transition metal-based HER catalyst. x In P, P and Co sites play the roles of proton acceptors and hydride acceptors, respectively. The negatively charged P atoms weaken the chemical bond strength between Co and H, thus promoting the desorption process of H. x Most P-based catalysts exhibit excellent HER activity in alkaline and acidic electrolytes, and their HER activity in neutral media still needs to be further improved.

[0004] There are two main strategies for improving the activity of electrocatalysts: improving intrinsic electrocatalytic activity and increasing the number of catalytic active sites. For the HER reaction in neutral electrolyte, it mainly includes water adsorption / dissociation (Volmer) and hydrogen adsorption / desorption steps. It is generally believed that the Volmer step is the rate-determining step in neutral HER. Therefore, it is hoped that the Co2+ reaction rate can be improved by introducing species with strong water adsorption and dissociation capabilities. x The intrinsic electrocatalytic activity of P.

[0005] RuO2 is an excellent OER catalyst and theoretically has a promoting effect on the dissociation of water. In the present invention, RuO2 is introduced into Co x Heterostructures constructed in P to enhance Co x The intrinsic HER active sites of the P catalyst are improved by preparing structures with large specific surface areas such as arrays, porous structures, and ultra-thin nanosheets to enhance the contact between the catalyst and the electrolyte, thereby enhancing the HER activity. Summary of the invention

[0006] In order to solve the problems in the prior art, the present invention proposes a HER electrocatalyst with a porous heterogeneous structure and a preparation method thereof.

[0007] Technical solution: A method for preparing a HER electrocatalyst with a porous heterogeneous structure, comprising the following steps:

[0008] Step 1, removing oxides on the surface of nickel foam;

[0009] Step 2: Using cobalt nitrate hexahydrate, urea, nickel foam and ruthenium chloride as raw materials, a solvothermal method is used to prepare Ru-doped basic cobalt carbonate nanowire arrays;

[0010] Step 3, heating the Ru-doped basic cobalt carbonate nanowire array in a muffle furnace to obtain a RuO2 / Co3O4 nanowire array;

[0011] Step 4: Place the RuO2 / Co3O4 nanowire array and NaH2PO2 in a crucible, anneal and phosphate in a nitrogen gas stream to obtain RuO2 / Co x P / Co3O4 nanowire arrays;

[0012] Step 5: RuO2 / Co x P / Co3O4 nanowire arrays were acid-washed to remove Co3O4 and obtain RuO2 / Co x P nanowire arrays, HER electrocatalysts with porous heterostructures.

[0013] Preferably, the specific operations of step one are as follows:

[0014] First, the nickel foam was cut into sheets of 2×3 cm in size, placed in anhydrous ethanol for ultrasonic treatment for 5 minutes, and then rinsed repeatedly with deionized water several times; then, the nickel foam was placed in a 2M hydrochloric acid solution for ultrasonic treatment for 10 minutes, followed by anhydrous ethanol for ultrasonic treatment for 5 minutes, and then rinsed repeatedly with deionized water several times, and the anhydrous ethanol ultrasonic treatment and deionized water cleaning were repeated many times.

[0015] Preferably, the specific operations of step 2 are as follows:

[0016] Step 2.1, pour 1 mol of cobalt nitrate hexahydrate and 5 mol of urea into 40 ml of deionized water, stir until completely dissolved, and then add 1.12-5.6 mL of RuCl3·xH2O solution dropwise. The concentration of RuCl3·xH2O solution is 10 mg·mL -1 ;

[0017] Step 2.2, pour the solution obtained in step 2.1 into a polytetrafluoroethylene high-pressure reactor, and then place the nickel foam in the reactor; prepare the Ru-doped basic cobalt carbonate nanowire array by a solvent thermal method at 90°C for 7h.

[0018] Preferably, in step 2.1, the volume of the RuCl3·xH2O solution is 3.38 mL.

[0019] Preferably, in step 3, the Ru-doped basic cobalt carbonate nanowire array is heated in a muffle furnace at a temperature of 350°C and a heating rate of 5°C·min -1 Heat for 3h.

[0020] Preferably, in step 4, the weight ratio of RuO2 / Co3O4 nanowire array to NaH2PO2 is 1:10; the conditions for annealing and heat preservation in nitrogen flow are: 5°C·min in nitrogen flow -1 The heating rate was 300 °C for annealing and the temperature was kept at 2 h.

[0021] Preferably, the pickling conditions in step five are: pickling in a 2M HCl solution for 10 minutes.

[0022] Beneficial effect: The present invention constructs a heterogeneous structure RuO2 / Co x P improves Co x The intrinsic electrocatalytic activity of P was enhanced by constructing a porous nanowire array structure to expose more active sites of the catalyst. x Excellent HER activity of P catalyst in neutral electrolyte. Porous RuO2 / Co x The P nanowire array only needs 8mV and 81mV overpotential to achieve 10mA cm -2 and 100mA·cm -2 The current density is 500 mA cm -2 The catalyst exhibited good stability at industrial current density (continuous catalytic HER for 120 hours). The reasons for the enhanced neutral HER activity were analyzed by in situ Raman, in situ EIS and KIE. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 RuO2 / Co x TEM image of P.

[0024] Figure 2 RuO2 / Co x Electrochemical performance diagram of P.

[0025] Figure 3 RuO2 / Cox P electrocatalytic stability.

[0026] Figure 4 RuO2 / Co x P and Co x In-situ Raman data of P at different potentials, where (a) is RuO2 / Co x In situ Raman spectra of P at different potentials, (b) Co x In situ Raman spectra of P at different potentials, (c) RuO2 / Co at open circuit voltage (OCP) x Fitting of three OH stretching modes of water at the P interface; (d) RuO2 / Co x P (left) and Co x P (right) Normalized intensity of the three peaks of interfacial water as a function of potential.

[0027] Figure 5 RuO2 / Co x In situ electrochemical impedance spectroscopy of P.

[0028] Figure 6 RuO2 / Co x LSV curves of RuO2 / CoxP in 1M PBS / H2O and 1M PBS / D2O and the corresponding KIE values. (a) LSV curves of RuO2 / CoxP in 1M PBS / H2O and 1M PBS / D2O; (c) LSV curves of CoxP in 1M PBS / H2O and 1M PBS / D2O; (b) LSV curves of RuO2 / CoxP in 1M PBS / H2O and 1M PBS / D2O. 2 / (d) is the KIE value corresponding to CoxP, and (d) is the KIE value corresponding to CoxP.

[0029] Figure 7 For Co x P, RuO2 / Co x P / Co3O4, RuO2 / Co x LSV curves of P, Pt / C and NF.

[0030] Figure 8 RuO2 / Co x P and Co x In situ EIS diagram of P, where (a) is RuO2 / Co x In situ EIS diagram of P, (b) of Co x In situ EIS graph of P.

[0031] Fig. 9 RuO2 / Co x P、RuO2 / Co x P-1 and RuO2 / Co xElectrochemical performance test results of P-2. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is described in detail below through embodiments, but the protection scope of the present invention is not limited to the embodiments.

[0033] Example 1

[0034] This embodiment provides a HER electrocatalyst with a porous heterostructure. x P and RuO2 / Co x Preparation method of P nanowire array. The specific preparation method is as follows:

[0035] Step 1: Remove oxides from the surface of nickel foam.

[0036] The nickel foam was cut into a size of 2 cm × 3 cm (the thickness of the nickel foam was 1.5 mm), and the oxide on the surface was washed away by a specific process. The nickel foam was purchased from "Sheng Ernuo Energy Mall".

[0037] The specific process in this embodiment specifically refers to: placing the cut nickel foam in anhydrous ethanol for ultrasonic treatment for 5 minutes, and then repeatedly rinsing with DIW (deionized water). Then, the nickel foam is placed in a 2M hydrochloric acid solution for ultrasonic treatment for 10 minutes, followed by ultrasonic treatment with anhydrous ethanol, each time for 5 minutes, and repeatedly rinsed with DIW (deionized water), and the anhydrous ethanol ultrasonic treatment and DIW cleaning are performed 3 times each.

[0038] Step 2: Using cobalt nitrate hexahydrate, urea, nickel foam and ruthenium chloride as raw materials, a solvothermal method is used to prepare basic cobalt carbonate and Ru-doped basic cobalt carbonate nanowire arrays.

[0039] 1) Preparation method of Ru-doped basic cobalt carbonate nanowire array:

[0040] Step 2.1: First, pour 1 mol of cobalt nitrate hexahydrate and 5 mol of urea into 40 ml of DIW and stir until completely dissolved. Then, add 3.38 mL of RuCl3·xH2O (10 mg·mL -1 ) solution was added dropwise into the above solution.

[0041] Step 2.2, pour the stirred solution into a polytetrafluoroethylene high-pressure reactor, and then place a piece of treated nickel foam (2cm×3cm, thickness 1.5mm) in the reactor; prepare Ru-doped basic cobalt carbonate nanowire arrays by a solvent thermal method at 90℃ for 7h.

[0042] 2) Preparation method of basic cobalt carbonate nanowire array: In step 2.1, without adding RuCl3·xH2O solution, the rest of the process is carried out according to steps 2.1 to 2.2 of step 2 to obtain basic cobalt carbonate nanowire array.

[0043] Step 3: The prepared basic cobalt carbonate and Ru-doped basic cobalt carbonate nanowire array were placed in a muffle furnace at 350°C with a heating rate of 5°C min. -1 After heating for 3 h, cobalt trioxide (Co3O4) and ruthenium dioxide / cobalt trioxide (RuO2 / Co3O4) nanowire arrays were obtained.

[0044] Step 4: Then, the Co3O4 and RuO2 / Co3O4 nanowire arrays prepared above were placed in a crucible with sodium hypophosphite (NaH2PO2) at a certain weight ratio (1:10) and heated in a nitrogen flow at 5°C min -1 The heating rate was annealed at 300 ° C and kept at this temperature (phosphating time) for 2 hours to obtain Co x P / Co3O4 and RuO2 / Co x P / Co3O4 nanowire arrays.

[0045] Step 5: Prepare the Co x P / Co3O4 and RuO2 / Co x The P / Co3O4 nanowire arrays were placed in a certain concentration (2M) of HCl solution for acid washing for 10 min to remove Co3O4 and obtain porous Co x P and RuO2 / Co x P nanowire array. RuO2 / Co x The P nanowire array is the HER electrocatalyst with a porous heterostructure described in the present invention.

[0046] According to the method of steps 1 to 5 above, the RuO2 / Co ... x P-1 and RuO2 / Co x P-2 nanowire array. Specifically, RuCl3·xH2O (10 mg·mL -1 ) solution was changed to 1.12 mL, and finally RuO2 / Co x P-1 nanowire array. RuCl3·xH2O (10 mg·mL -1 ) solution was changed to 5.6 mL, and finally RuO2 / Co x P-2 nanowire array.

[0047] The RuO2 / Co prepared in this example x TEM image of P, such as Figure 1 As shown. RuO2 / Co x P-1 nanowire array and RuO2 / Co x TEM images of P-2 nanowire arrays and RuO2 / Co x The TEM images of P are similar, but RuO2 / Co x The TEM image of the P material is more loose and porous, and the ultra-thin nanosheet structure is clearer. This ultra-thin nanosheet structure can increase the number of active sites exposed by the catalyst and promote the mass transfer rate.

[0048] Example 2

[0049] This example tests the porous Co x P and RuO2 / Co x Performance of P nanowire arrays.

[0050] The porous Co grown in situ on nickel foam in Example 1 x P and RuO2 / Co x The P nanowire array (the size used in the test was 2 cm × 0.2 cm, cut from the nanowire array prepared in Example 1) was used as the working electrode for subsequent electrochemical performance tests. Neutral electrolyte preparation: 9.6 g of disodium hydrogen phosphate and 11.36 g of sodium dihydrogen phosphate were weighed and gradually added to 80 mL of DIW to dissolve, and then 0.2 mol·L -1 The pH of the sodium hydroxide solution was adjusted to 7.0 and stirred thoroughly to obtain a 1M phosphate buffer solution (PBS) electrolyte. The electrochemical performance and stability of the catalyst were then tested using a Chenhua electrochemical workstation and a Cost electrochemical workstation. The reasons for the enhanced neutral HER activity were characterized and analyzed using in situ Raman, in situ electrochemical impedance spectroscopy (EIS) and kinetic isotope effect (KIE) tests.

[0051] Electrocatalytic performance characterization: HER activity was tested in a three-electrode system in a N2-saturated electrolyte using a Shanghai Chenhua workstation (CHI 760E). All samples were activated using cyclic voltammetry (CV) before electrochemical performance testing. The polarization curves (LSV) were plotted at 5 mV·s in different electrolytes. -1 The LSV curve at high current density was tested by using a Coster workstation. The Tafel slope curve is obtained by taking the logarithm of the LSV curve. According to the Butler-Volmer formula, the Tafel slope value is obtained by fitting the following equation:

[0052] η=a+blogj

[0053] In the formula, η represents the overpotential, j represents the current density, and b is the Tafel slope. The smaller the Tafel slope, the smaller the change of the overpotential with the increase of the current density, indicating that the catalyst has good catalytic performance. The stability of the catalyst is tested by chronoamperometry or chronopotentiometry using the Cost workstation.

[0054] Electrochemical impedance spectroscopy (EIS) test: The EIS spectrum was tested using a Chenhua workstation, and the experimental test was carried out under the conditions of a frequency range of 0.01 to 105 Hz and an amplitude of 5 mV. The 30 mA cm -2 The overpotential corresponding to the current density is set as the test voltage. During the in-situ EIS test, the test potential is tested from low overpotential to high overpotential and data is collected.

[0055] Kinetic isotope effect (KIE) experiment: KOH / H2O and KOD / D2O or PBS / H2O and PBS / D2O were used as electrolytes. The rate constants KH and KD in each solution were tested independently, and the KIE value was obtained by calculating the ratio of the two.

[0056] In-situ electrochemical Raman characterization: The instrument model for collecting in-situ Raman spectroscopy data was In Via, the laser wavelength was 532nm, and the data collection duration was 20s. x P is directly used as the working electrode. When the test solution of the Raman electrolytic cell is 1M KOH, the Hg / HgO electrode is selected as the reference electrode; when the test solution is 1M PBS, the Ag / AgCl electrode is selected as the reference electrode. Carbon rods are selected as counter electrodes in both alkaline and neutral electrolytes. During the test, the Raman cell always remains sealed. An electrochemical workstation is used to apply a constant voltage signal to the working electrode. First, the Raman spectrum is obtained at an open circuit voltage, and then the test is carried out from low voltage to high voltage in sequence to obtain the Raman spectrum in real time. Each voltage is maintained for 5 minutes, and Raman starts to collect data after 300 seconds. In order to avoid accidental errors and bubble interference, the Raman test is repeated three times at the same potential.

[0057] The test results are as follows Figure 2-Figure 9 As shown:

[0058] Figure 2-Figure 9 In, Co x P and RuO2 / Co x P was prepared as in Example 1, RuO2 / Co x P / Co3O4 is RuO2 / Co x P The previous product before pickling, preparation of RuO2 / Co xP and RuO2 / Co x When P / Co3O4, add RuCl3·xH2O (10 mg·mL -1 )The volume of the solution is 3.38 mL.

[0059] 1)RuO2 / Co x The electrochemical performance of P is shown in the figure Figure 2 As shown; RuO2 / Co x Electrocatalytic stability of P Figure 3 shown.

[0060] from Figure 2 It can be seen that in the neutral 1M PBS electrolyte, RuO2 / Co x P can reach 10 and 100 mA cm at ultra-low overpotentials of 8 mV and 81 mV, respectively. -2 The current density of RuO2 / Co x P has high activity. Figure 3 It can be seen that RuO2 / Co x P in neutral 1M PBS electrolyte, 500mA·cm -2 The RuO2 / Co x P has excellent durability.

[0061] 2)RuO2 / Co x The in situ electrochemical impedance spectroscopy of P Figure 5 shown.

[0062] By RuO2 / Co x P was subjected to in situ EIS test to explore its basic elementary reactions in the HER reaction process. Figure 5 It can be clearly seen that RuO2 / Co x P shows two phase angles, corresponding to the Volmer-Heyrovsky mechanism, which is in good agreement with the Tafel slope value. x The phase angle of P decreases rapidly with the increase of overpotential in the medium frequency region, indicating that the Volmer step is the RuO2 / Co x P is the rate-determining step in the neutral HER reaction.

[0063] 3)RuO2 / Co x The LSV curves and corresponding KIE values ​​of P in 1M PBS / H2O and 1M PBS / D2O are shown in Figure 6 shown.

[0064] The proton transfer kinetics during water dissociation was studied by KIE measurement. Figure 6). RuO2 / Co is calculated to be x The average KIE value of P is 2.08, which is lower than that of Co x The average KIE value of P (2.23) indicates that RuO2 / Co x P has faster water dissociation kinetics.

[0065] 4)RuO2 / Co x In situ Raman spectra of P at different potentials are shown in Figure 4 shown.

[0066] In situ Raman spectroscopy was used to monitor the dynamic reaction pathway of the catalyst during the HER process. x P and Co x The in situ Raman data of P are shown in Figure 4 As shown in a and b, at ~3400cm -1 The broad peak at 3250cm belongs to the interfacial water. It can be fitted into three characteristic peaks: -1 Tetrahedral coordinated water (V1) at 3450cm -1 The trihedral coordinated water (V2) and the -1 The dangling OH bond (V3) at the position of the HER is shown in Figure 2. Among them, V1 and V2 represent the active water molecules catalyzed by HER, and V3 represents the inactive water molecules ( Figure 4 c) relative to Co x P, RuO2 / Co x P at ~3400cm -1 The intensity of the interfacial water peak observed at the RuO2 / Co x The water on the P surface is rapidly consumed. In particular, RuO2 / Co x The intensity of the V3 peak of P decreases faster with the negative increase of voltage, which indicates that the x Rapid water dissociation occurred on the P surface ( Figure 4 d), thus showing a better performance than Co x Faster HER reaction kinetics.

[0067] 5) Co x P, RuO2 / Co x P / Co3O4, RuO2 / Co x The LSV curves of P, Pt / C (commercial platinum carbon, purchased from McLean) and NF (NF is the abbreviation of nickel foam), such as Figure 7 As shown, RuO2 / Co x P exhibits the best hydrogen evolution (HER) performance. In 1M PBS electrolyte, RuO2 / Co xP only needs ultra-low overpotentials of 8 mV and 81 mV to reach 10 and 100 mA cm, respectively. -2 The current density of Co x P requires an overpotential of 75 and 175 mV to achieve the same current density, indicating that the introduction of RuO2 can effectively improve the x The neutral HER activity of P. It is worth noting that at different current densities, RuO2 / Co x The overpotential of P is even lower than that of commercial Pt / C catalyst, which further illustrates that RuO2 / Co x The high activity of P.

[0068] 6) Figure 8 RuO2 / Co x P and Co x In situ EIS diagram of P, where (a) is RuO2 / Co x In situ EIS diagram of P, (b) of Co x In situ EIS graph of P.

[0069] By RuO2 / Co x P and Co x P was subjected to in situ EIS test to explore its basic elementary reactions in the HER reaction process. Figure 8 It can be clearly seen that RuO2 / Co x P and Co x P shows two phase angles, corresponding to the Volmer-Heyrovsky mechanism, which is in good agreement with the Tafel slope value. x Compared with the phase angle of P, RuO2 / Co x The phase angle of P decreases rapidly with the increase of overpotential in the medium frequency region, indicating that the Volmer step is the RuO2 / Co x P is the rate-determining step in the neutral HER reaction.

[0070] 7)RuO2 / Co x P、RuO2 / Co x P-1 and RuO2 / Co x Electrochemical performance test of P-2.

[0071] The results are as follows Fig. 9 As shown in the figure above, compared with RuO2 / Co x P-1 and RuO2 / Co x P-2, RuO2 / Co x P has better HER electrochemical performance.

[0072] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes may be made to the form and details without departing from the spirit and scope of the present invention.

Claims

1. A method for preparing a HER electrocatalyst having a porous heterostructure, characterized in that: The steps include: Step 1, removing oxides on the surface of nickel foam; Step 2: Using cobalt nitrate hexahydrate, urea, nickel foam and ruthenium chloride as raw materials, a solvothermal method is used to prepare Ru-doped basic cobalt carbonate nanowire arrays; Step 3, heating the Ru-doped basic cobalt carbonate nanowire array in a muffle furnace to obtain a RuO2 / Co3O4 nanowire array; Step 4: Place the RuO2 / Co3O4 nanowire array and NaH2PO2 in a crucible, anneal and phosphate in a nitrogen gas stream to obtain RuO2 / Co x P / Co3O4 nanowire arrays; Step 5: RuO2 / Co x P / Co3O4 nanowire arrays were acid-washed to remove Co3O4 and obtain RuO2 / Co x P nanowire arrays, HER electrocatalysts with porous heterostructures.

2. The preparation method according to claim 1, characterized in that: The specific operation of step 2 is as follows: Step 2.1: Pour 1 mol of cobalt nitrate hexahydrate and 5 mol of urea into 40 ml of deionized water, stir until completely dissolved, and then add 1.12-5.6 mL of ruthenium trichloride hydrate solution dropwise. The concentration of the ruthenium trichloride hydrate solution is 10 mg mL -1 ; Step 2.2, pour the solution obtained in step 2.1 into a polytetrafluoroethylene high-pressure reactor, and then place the nickel foam in the reactor; prepare the Ru-doped basic cobalt carbonate nanowire array by a solvent thermal method at 90°C for 7h.

3. The preparation method according to claim 2, characterized in that: In step 2.1, the volume of the ruthenium trichloride hydrate solution is 3.38 mL.

4. The preparation method according to claim 1, characterized in that: The specific operation of step one is as follows: The nickel foam was cut into sheets, ultrasonically treated in anhydrous ethanol for 5 minutes, and then repeatedly rinsed with deionized water for several times; then, the nickel foam was ultrasonically treated in 2M hydrochloric acid solution for 10 minutes, followed by ultrasonic treatment in anhydrous ethanol for 5 minutes, and then repeatedly rinsed with deionized water for several times, and the anhydrous ethanol ultrasonic and deionized cleaning were repeated many times.

5. The preparation method according to claim 1, characterized in that: In the step 3, the Ru-doped basic cobalt carbonate nanowire array is heated in a muffle furnace at a temperature of 350°C and a heating rate of 5°C·min -1 Heat for 3h.

6. The preparation method according to claim 1, characterized in that: In the step 4: The weight ratio of RuO2 / Co3O4 nanowire arrays to NaH2PO2 is 1:10; The conditions for annealing and heat preservation in nitrogen flow are: 5℃·min -1 The heating rate was 300 °C for annealing and the temperature was kept at 2 h.

7. The preparation method according to claim 1, characterized in that: The pickling conditions in step 5 are: pickling in a 2M HCl solution for 10 minutes.

8. A HER electrocatalyst having a porous heterostructure prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of electric catalyst for acidic fully-decomposed water

    CN106694005A

  • Preparation method and application of Co3O4-RuO2 composite material

    CN114592210A